Combination of protein engineering and metabolic engineering to enhance (+)‐nootkatone production in Saccharomyces cerevisiae. Issue 2 (1st August 2022) - Guo, Jingyan; Zhou, Wei; Li, Yuanyi; Qin, Weichuang; Wei, Dongzhi; Wang, Fengqing; Gao, Bei
Abstract: The introduction of heterologous pathways into microorganisms for high‐level synthesis of valuable compounds would be extremely meaningful. However, the endogenous heterologous pathway conversion point frequently serves as a bottleneck that limits product synthesis. (+)‐Nootkatone is an important functional sesquiterpenoid with a unique grapefruit flavor, which is frequently used as a fragrance. The low catalytic efficiency of the valencene synthase CnVS, the first heterologous enzyme in the biosynthesis of (+)‐nootkatone, is the major challenge that restricts the production of (+)‐nootkatone in Saccharomyces cerevisiae . In this study, we modified CnVS on the basis of the catalytic environment and mechanism of the enzyme. The residue M560 involving in alkyl transfer during substrate cyclization was found to affect activity. By tuning the residue, mutant M560L exhibited a 60% increase in the unit cell yield of (+)‐valencene, which is the precursor of (+)‐nootkatone. Furthermore, multistep strategies of metabolic engineering were employed that transferred the metabolic flux to the target product synthesis pathway and displayed the superimposed effect of metabolic and protein engineering on (+)‐nootkatone yield. Finally, multicopy integration of tHMG1 and ERG20ERG20‐GSG‐CnVS M560L boosted the production of (+)‐nootkatone to 85.43 mg/L in flask and 804.96 mg/L (5.29 mg/[L h]) in bioreactor. In conclusion, this study presents a paradigm for constructing microbial cell factories using a combination of protein and metabolic engineering in S. cerevisiae . Abstract : This study focused on the conversion bottleneck of the natural‐heterologous pathway and achieved a significant boost in the yield of (+)‐nootkatone through a combination of protein modification and metabolic optimization strategy, which also shows great potential for the efficient microbial synthesis of other sesquiterpenoids.